Researching Pre-school Teachers’ Knowledge of Oral Language Pedagogy Using Video - Mathers, Sandra; Siraj, Iram (Frontiers in Education, 2021)
The Observing Language Pedagogy (OLP) tool uses videos of authentic classroom interactions to elicit the procedural knowledge which pre-school teachers can access, activate and use to support classroom decision-making. Three facets are captured: perceiving (the ability to identify salient language-supporting strategies); naming (the use of specific professional vocabulary to describe interactions); and interpreting (the ability to interpret the interactions observed). Prior research has shown that the OLP predicts classroom quality; with naming and interpreting proving the strongest predictors. This study examines OLP responses from 104 teachers to consider the nature of their pedagogical knowledge (perceiving, naming, interpreting), and describe differences between expert teachers (those leading language-supporting classrooms) and non-expert teachers (those leading lower quality classrooms). It offers insight into the nature of language-related expertise and to guide design of teacher professional development, suggesting a tri-fold focus on knowledge of linguistic input, relational pedagogy and cognitive challenging interactions.